Stress field characterization of the Hellisheidi geothermal field and possibilities to improve injection capabilities - Batir, Joseph Francis (2011)
Verkefnið er unnið í tengslum við Háskóla Íslands og Háskólann á Akureyri The earth is under constant stress in response to plate tectonics, gravitational loading, and other effects at a variety of length-scales. The type of stresses an area of the earth’s crust is under controls the formation, distribution, geometry and other characteristics of fractures in the earth. In many locations, and especially in geothermal systems, these fractures control fluid flow. Thus the mechanisms of their propagation and stresses that drive them need to be understood. In many high temperature regions that lack natural permeability this is a key to developing enhanced geothermal systems (EGS). Image log analysis has the ability to map the distribution and attitude of fractures, and to detect induced structures on the borehole walls that are indicators of the stress field in the vicinity of the borehole. Here, a case study is presented from the Hellisheidi geothermal field where image logs are used to detect the fracture network and orientation, and to map the stress states of the boreholes as an inference to the natural stress state. Four boreholes within the Kolvidarholl reinjection field had image log data, but only HN-16 is presented here because other logs were lower quality and therefore not examined with this study. HN-16 was drilled with a deviated well path complicating the relationship of induced structures within the wellbore to the in-situ stress state. The procedure to obtain a crust referenced stress measurement is given and results show that the Borehole Televiewer (BHTV) data supports surface manifestations of the stress field orientation. HN-16 is one of 7 wells in the Kolvidarholl reinjection area for the Hellisheidi Power Plant. While HN-16 is accepting sufficient fluids, the other reinjection wells are underperforming expectations. Results from this study suggest that the best scenario to increase injection capabilities of previous wells would be to increase the depth of the wells with a primary goal to ...